The role of branding in the choice of a university of technology - Cleopatra Moipone Matli (Ümit Hacıoğlu, 2021)
Brand choice has historically played an important role in a wide range of industries, particularly in the private sector, where billions of Rands are invested to entice potential customers. Taking this into consideration, the purpose of this study is to investigate the effect of brand awareness and brand image on first-year student selection of a University of Technology in KwaZulu-Natal. The objectives of the study were to establish and identify the brand preference and image attributes that entice first-year students’ selection of a University of Technology (UoT). The study also examined the biographic variables of those students. To accomplish these objectives, an exploratory study using a quantitative research approach was conducted, in which questionnaires were administered to 500 first-year students at the selected Universities of Technology in KwaZulu-Natal. The study revealed that topics such as investments in brand awareness and brand image, safety and security, the caliber of staff, delays in academic programmes, student-lecturer relationships, and service delivery were identified as factors that influenced the participants' selection and willingness to recommend their institutions to potential students. Thus, the study recommends that UoTs should pay more attention to branding strategies as an agendum to ensuring institutional profitability and viability, relationship management, and human resource.  Finally, the findings of this study are limited to KwaZulu-Natal and should not be extrapolated outside this region.